RSCHERICHIA COLI IN BROILER CHICKENS ‎ I- SEROLOGY AND ANTIBIOTIC SENSITIVITY - Hyder Al-Safi, Hazim; G. Abdul Ghani , Zeki; A. Al-Attar, Majed (The Iraqi Journal of Veterinary Medicine, 2024)
A study was dane on 300 cases of Colibacillosis in broiler chickens collected from poultry farms in Baghdad. Escherichia coli was isolated from all cases from heart blood. The highest incidence (45%) of the disease was noticed among the 3-4 weeks old chickens. The antibiotic sensitivity test revealed that all isolates were resistant to Chloramphenical, Tetracycline,Lincomycin and Erythromycin. Ninty five percent of the isolates were resistant to Sulfa Trimethoprim mixture and 40% to Ampicillin. Serotyping of some of the isolates showed that the serotypes 01, 02 and 078 were the most prevalent types; other serotypes were also identified especially 035, 036, 088 and 018.